A study of the productivity in stayrod manufacturing - Talib, Elyas (2010)
This report contains discusses about the productivity in the production line of Stayrod manufacturing using line balancing method. This project analyzed the problem that affects the productivity due to unbalance line. There were significant relationship between the processing time and the number of operators in production line. Current manufacturing system brings the line balancing ratio and line balancing efficiency is 63.09% and 81 .64% respectively; with the line balancing method, it shows an increase of line balancing ratio and line balancing efficiency to 80.04% and 94.41 % respectively. The simulation model was used to verify the result from the line balancing. Furthermore, this project also proposed some of the improvements in the production line regarding the line balancing such as idle time, working time, transfer time, and number of operators.